Infrastructure Facilities of the Community Protection Unit in the Implementation of Community Order and Peace in North Minahasa Regency - Rumuat, Merry; Kairupan, Sisca B.; Kandou, Selpius Ruslan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The focus of the researcher's problem is the Infrastructure Facilities of the Community Protection Unit in the Implementation of public order and tranquility in Airmadidi District. The method used in this research is to use a qualitative approach. The results showed that the infrastructure of the community protection unit through indicators of main task descriptions and functions, forms of support and stakeholder involvement had been carried out well, although in terms of budget it was still lacking and structuring the system of sharing authority in the source of funds for infrastructure facilities in each SKPD related to community protection unit facilities and infrastructure.